Mangás e animes : sociabilidade entre cosplayers e otakus - Winterstein, Claudia Pedro (2009)
The interest by the outbreak of a group of people that are admirers of the Japanese pop culture - especially by the comic books (mangas) and the cartoons (animes) is what led me to the developing of this research, in which my goal is to understand the logic of the sociability among the consumers of these medias, through the use of some very important anthropological concepts, such as the sociability, the cultural consume and life style. To do so, I started a study that began at the mangas and animes conventions, where the otakus meet to participate in contests and workshops, as well as to watch the animes and musical presentations, and also to discuss their own stories. Beyond the merely social nature, these conventions have eventually became the first step to those who wish to enter the pop culture universe, besides being a way of assertion of a specific juvenile condition to those who are already a part of it.